Ragam Bentuk Hegemoni dalam Karya Sastra di Semenanjung Persia dan Asia Tengah: The Kite Runner dan the Thief of Baghdad - Fakhruddin, Rifki Muhamad; Subawati, Salsabila Zahran Galuh Putri; Nurholis, Nurholis (Kajian Linguistik dan Sastra, 2025)
This article discusses the forms of hegemony that appear in literary works in the Persian Peninsula and Central Asia. The method used is descriptive qualitative. Factors such as geographical, social, and educational environments can give rise to social issues and hegemony. Literature, as social criticism as well as a reflection of society, often becomes a tool to promote or challenge hegemony. This approach uses the sociology of literature and Antonio Gramsci's theory of hegemony. The research data sources are the novels The Kite Runner by Khaled Hosseini and The Thief of Baghdad by Alexander Romanoff. The data were obtained using reading and note-taking techniques. The results of the research in the form of various forms of hegemony that appear in the two novels are five forms, namely: (1) racial hegemony, (2) educational hegemony, (3) socio-cultural hegemony, (4) gender role hegemony, and (5) political hegemony Abstrak Artikel ini membahas tentang bentuk-bentuk hegemoni yang muncul di dalam karya sastra di Semenanjung Persia dan Asia Tengah. Metode yang digunakan adalah deskriptif kualitatif. Faktor-faktor seperti lingkungan geografis, sosial, dan pendidikan dapat memunculkan isu sosial dan hegemoni. Sastra, sebagai kritik sosial serta cerminan masyarakat, seringkali menjadi alat untuk mempromosikan atau menantang hegemoni. Pendekatan ini menggunakan sosiologi sastra dan teori hegemoni Antonio Gramsci. Sumber data penelitian adalah novel The Kite Runner karya Khaled Hosseini dan The Thief of Baghdad karya Alexander Romanoff. Data diperoleh dengan teknik membaca dan mencatat. Hasil penelitian berupa ragam bentuk hegemoni yang muncul di dalam kedua novel adalah lima bentuk, yaitu: (1) hegemoni ras, (2) hegemoni pendidikan, (3) hegemoni sosial-kultural, (4) hegemoni peran gender, dan (5) hegemoni politik